1987
DOI: 10.1016/0378-1097(87)90489-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the presence of two distinct phosphoenolpyruvate: Mannose phosphotransferase systems in Streptococcus mutans GS5-2

Abstract: We have isolated a spontaneous 2-deoxyglucose (2DG) resistant mutant from Streptococcus mutans GS5-2, called GM500, that grew as well as the parental strain on mannose. Membranes of glucose-grown cells of the mutant strain were, however, unable to catalyse the phosphoenolpyruvate-dependent phosphorylation of mannose in the presence of purified enzyme I (El) and hydroxyproline (HPr) unlike the wild-type cells. Resting cells of strain GM500 were also unable to transport mannose after growth at the expense of glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
1
5
1
Order By: Relevance
“…Growth in 0.2% mannose was faster for JAM1 (doubling time Х180 min) than for the wild-type strain (doubling time Х255 min). This finding is in contrast with that reported for S. mutans GS-5, in which a spontaneously arising EII Man -deficient strain grew more slowly than the parent in glucose but growth in mannose was unaffected (23,24). Of note, no significant differences in growth rates were observed between the wild-type strain and JAM1 when 0.2% fructose was used as the sole carbohydrate source (Table 2).…”
Section: Characteristics Of Eiiabcontrasting
confidence: 86%
“…Growth in 0.2% mannose was faster for JAM1 (doubling time Х180 min) than for the wild-type strain (doubling time Х255 min). This finding is in contrast with that reported for S. mutans GS-5, in which a spontaneously arising EII Man -deficient strain grew more slowly than the parent in glucose but growth in mannose was unaffected (23,24). Of note, no significant differences in growth rates were observed between the wild-type strain and JAM1 when 0.2% fructose was used as the sole carbohydrate source (Table 2).…”
Section: Characteristics Of Eiiabcontrasting
confidence: 86%
“…These results suggested that strain GM500 was defective at the level of the mannose PTS and possessed a distinct glucose PTS that could transport glucose into the cell. The presence of a second inducible mannose PTS recently discovered in S. mutans GS5-2 might explain the fact that strain GM500 grew well on mannose (see Table 1) (23). The results of PTS activities obtained with strains 27352 and MM202 also indicated that the mutant strain MM202 was affected at the level of the mannose PTS, but possessed a distinct glucose PTS ( Table 2).…”
Section: Glucose Is Transported By Two Phosphoenoipyruvate: Phosphotrmentioning
confidence: 85%
“…For example, in L. lactis glucose can be imported via the mannose or cellobiose PTSs or the glucose permease GlcU (Castro et al, 2009). In S. mutans alone, PTS systems have been identified for glucose (Schachtele & Mayo, 1973), mannitol, glucitol (Brown & Wittenberger, 1973;Maryanski & Wittenberger, 1975), lactose (Calmes, 1978), sucrose (Slee & Tanzer, 1979;St Martin & Wittenberger, 1979), mannose (Vadeboncoeur, 1984;Néron & Glucose is either internalized and concomitantly phosphorylated the PTS systems (PtcABC or PtnABCD) or imported by the GlcU permease and phosphorylated by glucose kinase. PTS systems are represented by circles, while non-PTS sugar import systems are represented by squares.…”
Section: Sugar Importmentioning
confidence: 99%
“…Nomenclature used is for Lactococcus lactis. Vadeboncoeur, 1987), fructose (Gauthier et al, 1984a, b), maltose (Würsch & Koellreutter, 1985), and trehalose (Poy & Jacobson, 1990).…”
Section: Sugar Importmentioning
confidence: 99%